ESTUDO FITOQUÍMICO E ATIVIDADES BIOLÓGICAS DE DUAS ESPÉCIES DA FAMÍLIA ASTERACEAE - Feleti, Sula Maria Vieira (2020)
Galinsoga parviflora Cav. and Vernonia polyanthes (Spreng.) Less are medicinal plants belonging to the Asteraceae family that show several biological activities. This study aimed to perform the chemical characterization of G. parviflora and V. polyanthes